Stereoselectivity of Pseudomonas cepacia lipase toward secondary alcohols: a quantitative model. - Schulz, T. (Cold Spring Harbor Laboratory Press, 2000)
The lipase from Pseudomonas cepacia represents a widely applied catalyst for highly enantioselective resolution of chiral secondary alcohols. While its stereopreference is determined predominantly by the substrate structure, stereoselectivity depends on atomic details of interactions between substrate and lipase. Thirty secondary alcohols with published E values using P. cepacia lipase in hydrolysis or esterification reactions were selected, and models of their octanoic acid esters were docked to the open conformation of P. cepacia lipase. The two enantiomers of 27 substrates bound preferentially in either of two binding modes: the fast-reacting enantiomer in a productive mode and the slow-reacting enantiomer in a nonproductive mode. Nonproductive mode of fast-reacting enantiomers was prohibited by repulsive interactions. For the slow-reacting enantiomers in the productive binding mode, the substrate pushes the active site histidine away from its proper orientation, and the distance d(H(N epsilon) - O(alc)) between the histidine side chain and the alcohol oxygen increases, d(H(N epsilon) - O(alc)) was correlated to experimentally observed enantioselectivity: in substrates for which P. cepacia lipase has high enantioselectivity (E > 100), d(H(N epsilon) - O(alc)) is >2.2 A for slow-reacting enantiomers, thus preventing efficient catalysis of this enantiomer. In substrates of low enantioselectivity (E < 20), the distance d(H(N epsilon) - O(alc)) is less than 2.0 A, and slow- and fast-reacting enantiomers are catalyzed at similar rates. For substrates of medium enantioselectivity (20 < E < 100), d(H(N epsilon) - O(alc)) is around 2.1 A. This simple model can be applied to predict enantioselectivity of P. cepacia lipase toward a broad range of secondary alcohols.